2005
DOI: 10.1038/sj.bjc.6602820
|View full text |Cite
|
Sign up to set email alerts
|

The clinical potential of antiangiogenic fragments of extracellular matrix proteins

Abstract: Neovasculature development is a crucial step in the natural history of a cancer. While much emphasis has been placed on proangiogenic growth factors such as VEGF, it is clear that endogenous angiogenesis inhibitors also have critical roles in the regulation of this process. Recent research has identified several cryptic fragments of extracellular matrix/vascular basement membrane proteins that have potent antiangiogenic properties in vivo. It has become apparent that many of these fragments signal via interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 41 publications
1
37
0
Order By: Relevance
“…Recently, several ECM protein fragments with potent antiangiogenic properties have been isolated. These antiangiogenic properties were apparent only after proteolytic cleavage of their parental molecules (32). One study (33) showed that fragments of fibronectin were potent inhibitors of endothelial cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several ECM protein fragments with potent antiangiogenic properties have been isolated. These antiangiogenic properties were apparent only after proteolytic cleavage of their parental molecules (32). One study (33) showed that fragments of fibronectin were potent inhibitors of endothelial cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 These studies demonstrated that no clinically significant toxicities were associated with the administration of endostatin. 41 For example, among a group of 15 patients who received a total of 50 monthly cycles of daily 20-minute intravenous injections with doses ranging from 15 to 240 mg/m 2 per day experience only transient skin rashes at the highest doses.…”
Section: Clinical Experience: Endostatinmentioning
confidence: 91%
“…We will discuss angiostatin and endostatin briefly here. For recent reviews of these and other antiangiogenic molecules, see Clamp and Jayson (2005), Folkman (2005), Ruegg et al (2006), Sim (1998).…”
Section: Formation Of Antiangiogenic Molecules During Tumourinduced Amentioning
confidence: 99%